Organisational structure in relation to performance of the professional football clubs in the Kroatian first league - Siric, Z. (Acta Kinesiologica, 2013)
Nowadays football is not just a sport, but it has become involved in the market sphere, and therefore its quality depends on the performance of club`s organization and management. Question of organization and management of football clubs are top issue today at different societal levels. The aim of this research is to explore characteristics of the organizational structure of professional football clubs in the Croatian First League in relation to performance measures. The research was conducted on 19 football clubs in the Croatian First League trough a five year period from 2007/8 to 2011/12 championship season. Throughout this period 11 out of 19 football clubs were continuously present in the First League. Results revealed that the football clubs in the Croatian First League are not uniform in terms of organizational structure, but there are interclub differences in the number and type of organizational units. According to organizational type, eight clubs began the process of transformation from the Sport association to sports joint-stock company, and four clubs finished the reforming process, and now they are sports joint-stock company. As for specific organizational units, certain services have all clubs (administrative, financial, sports), but often lacks the marketing service. Organizational size in terms of units was not significantly correlated to financial measures, but ranking and income are significantly correlated. Significant positive correlationwas found between Club placement on ranking list for nearby seasons with exception for 2011/12 season.